Enhancing sugarcane harvest and load scheduling efficiency: a linear programming approach in East Java, Indonesia - Bambang Heri Purnomo; Lituhayu Supartiningrum (AGROINTEK, 2025)
Managing sugarcane harvesting and loading activities can increase the efficiency of sugar factory production. Scheduling this activity has a significant impact on reducing harvesting and loading costs, reducing the area of harvested land, and optimizing sugar production capacity. This study was conducted at a private sugar factory in Malang to develop a sugarcane harvesting and loading scheduling model. This model aims to optimize the sugar harvesting and transport scheduling so that the cost is lower and the sugar production capacity can be met. The model is built using LINGO 11.0 software. The results of the study showed significant improvements, namely the cost of harvesting and loading sugarcane decreased by 33.1% from Rp.  1.90 billion to Rp. 1.27 billion. Meanwhile, the harvested area decreased from 139.69 ha to 137.87 ha. In addition, sugarcane production increased by 24.6% from 11,140 tons to 13,887 tons per milling season, and the need for vehicles decreased by 39% from 2,870 to 1,736 units. The simulation results were then formed into a table containing a detailed schedule of harvesting and loading sugarcane as a recommendation to improve operational efficiency and factory profitability.